Aplikasi Modul Pengguna pada Perpustakaan Universitas Kristen Petra - Yanwar, Kevin; Dewi, Lily Puspa; Purba, Kristo Radion (Jurnal Infra, 2016)
Currently, Petra Christian University Library provides a form for its users to recommend collection. However, this process is still done manually which causes frequent human error and difficulties in processing. In addition, user has not been able to obtain information about the loans status, including the return date and fines, if any. Based on those problems, the authors made a library user module application.This website application is created using Yii Framework and PostgreSQL database. For book collection recommendation system is based on the collection titles of userâs history loans which is processed by Solr application and userâs interest classification. The live chat feature is built using PHP Socket and HTML5 WebSocket.The final result of this application development is users can create a new collection recommendation and view collection recommendation that have been proposed along with its status. Users can also view their status and history loans as well as the book collection recommendations. Moreover, there is a live chat feature as a form of communication media between the library with its users interactively.